Analisis Karakteristik Personal Donald Trump Dalam Kebijakan Protecting The Nation From Foreign Terrorist Entry Into The United States - Fadil, Ilham; Susiatiningsih, Rr. Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The United States is a democracy country which rescpect for human rights. One of the manifestation is the right of entry for imigrants seeking asylum. However, Trump’s administration didn’t reflect this. Through his authority, he issued Protecting The Nation From Foreign Terrorist Entry Into The United States by citing citing the national security. The perspective of relationship between policy and personality of the president is an interesting research objeck to study. It will be revealed in this study through the key questions about how personal characteristics of Donald Trump in taking the policy. The aim of this study is to explain the characteristics of leaders in relation to policy. This study uses qualitative methods with the type of explanatory research In compiling their arguments, researchers used the concept of Margaret Hermann (1980)